The Predictive and Prognostic Value of the Systemic Immune-Inflammation Index for Congestive Heart Failure - Zhihao Zheng; Shanshan Shi; Zechen Liu; Yanjun Song; Zhen’ge Chang; Kongyong Cui; Chenxi Song; Jia Li; Kefei Dou (Reviews in Cardiovascular Medicine)
Background: The systemic immune-inflammatory index (SII), calculated by (platelet count × neutrophil count)/lymphocyte count, is a novel biomarker with predive and prognostic value in numerous diseases. However, the relationship between SII and congestive heart failure (CHF) is not clear. This study aims to document the association of SII with the prevalence of CHF in the whole population and the long-term prognosis in CHF patients. Methods: This study included 57,500 participants in the National Health and Nutritional Examination Surveys, who were categorized into 3 categories based on their SII levels. A cross-sectional study was conducted to examine the relationship between SII and CHF prevalence in the whole population, followed by a prospective longitudinal study with a 5.4-year follow-up period for CHF patients to assess the predictive significance of SII for CHF. The main focus of the longitudinal study was on all-cause death as the primary outcome, with cardiovascular (CV) death as the secondary outcome. Associations were estimated using multivariate logistic regression and Cox proportional hazards models. The dose-response relationship was assessed with the restricted cubic spline (RCS) analysis. Results: In the cross-sectional analysis, there were 1927 (3.35%) participants diagnosed with CHF. The high SII group showed a significantly higher prevalence of CHF than the low SII group (odds ratio (OR) 1.24, 95% confidence interval (CI): 1.05, 1.45). In the longitudinal analysis, 882 all-cause deaths including 379 CV deaths were collected among CHF patients, and high SII was associated with a significant increase in the risk of all-cause death (hazard ratio (HR) 1.44; 95% CI: 1.14, 1.81) and CV death (HR 1.31; 95% CI: 1.08, 1.58). RCS confirmed the positive correlation of SII with the prevalence of CHF in the whole population, as well as the mortality risk in CHF patients. Conclusions: This study is the first to reveal that high SII was related to a high prevalence of CHF and a poor prognosis in CHF patients. These findings underscore the potential role of SII in the prevention and management of CHF.